1991
DOI: 10.1111/j.1533-8525.1991.tb00358.x
|View full text |Cite
|
Sign up to set email alerts
|

How Education Affects Attitude to Protest: A Further Test

Abstract: In a previous study, the authors found that among whites education affected attitude to protest in four ways: by raising commitment to civil liberties; by reducing support for violence; by increasing knowledge of protest justifications; and by altering a person's position in society, hence one's interests and identifications. This study shows that the same set of forces accounts for the variability of correlations between education and protest attitudes among samples of black respondents. Differences in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…If that is the case, then we would not expect to find differences in the acceptance of protest among groups characterized by social locations such as race, class, gender, and age; instead, we would expect that acceptance of protest is more widespread (Meyer and Pullum 2015). However, previous research on public opinion about protest shows that some individual characteristics such as age, race, occupation, and education are statistically significant predictors of attitudes toward protest (Hall, Rodeghier, and Useem 1986;Rodeghier, Hall, and Useem 1991). Hall et al (1986) in particular explain four possible mechanisms for how education, which has been found to be the most important predictor of such attitudes, affects attitudes toward protest: more education is associated with 1) stronger support of civil and political liberties; 2) intolerance of violence; 3) more identification with protest; and 4) more knowledge of the justifications for protest (see also Hall and Rosenthal 1981).…”
Section: Hypothesesmentioning
confidence: 92%
“…If that is the case, then we would not expect to find differences in the acceptance of protest among groups characterized by social locations such as race, class, gender, and age; instead, we would expect that acceptance of protest is more widespread (Meyer and Pullum 2015). However, previous research on public opinion about protest shows that some individual characteristics such as age, race, occupation, and education are statistically significant predictors of attitudes toward protest (Hall, Rodeghier, and Useem 1986;Rodeghier, Hall, and Useem 1991). Hall et al (1986) in particular explain four possible mechanisms for how education, which has been found to be the most important predictor of such attitudes, affects attitudes toward protest: more education is associated with 1) stronger support of civil and political liberties; 2) intolerance of violence; 3) more identification with protest; and 4) more knowledge of the justifications for protest (see also Hall and Rosenthal 1981).…”
Section: Hypothesesmentioning
confidence: 92%
“…Organizations and individuals throughout history have often supported the use of and education about nonviolent tactics, which, as recent research has shown, can be successful at influencing political change (Chenoweth and Stephan 2011). Higher levels of education have been shown to decrease individual level support for violent protest but to increase support for protest among those lacking close relationships to protesters (Rodeghier, Hall, and Useem 1991). Dalton, Van Sickle, and Weldon (2010) find that education levels are associated with increased protest participation.…”
Section: Why Women Protestmentioning
confidence: 99%
“…Age, for example, is associated with the willingness to support protests (Hall, Rodeghier, & Useem, 1986; Rodeghier, Hall, & Useem, 1991) as well as with Internet use (Katz & Rice, 2002). Educational attainment is positively related to willingness to support protests because education increases commitment to civil liberties, decreasing support of use of violence, increasing knowledge of protestors' grievances (Hall et al, 1986; Rodeghier et al, 1991). Educational attainment is also positively related to Internet use (Katz & Rice, 2002; Rice & Katz, 2003).…”
Section: Networked Authoritarianismmentioning
confidence: 99%